Pengembangan Bahan Ajar IPS Model Shared Kelas VIII - Aziz Aziz; Pargito Pargito; Risma M Sinaga (Jurnal Studi Sosial / Journal of Social Studies, 2017)
This study aims to develop teaching materials of social studies use model Shared class VIII SMP with the theme "Environment and Community Economic Activities" is feasible and interesting, and foster self-reliance in students in learning based on the test of material and media expert, And students viewed from the aspects of material / content, language, presentation, and graphic. The research method used is Research and Development (R D) Borg and Gall. Module development design and procedures follow the development steps of Hilda Taba. Technique of data collection is done by using interview technique, observation, and questionnaire. The data analysis technique uses quantitative descriptive data analysis expressed in the five scale scores. The results of the module feasibility test by the material expert obtained the assessment with the category of "good", the media experts obtained the category of "very good", teacher and students assessment get the category "good". Based on feasibility tests by experts, teachers and students indicates that the IPS module model shared of VIII class is very systematic, consistent, interesting, highly appropriate, and very appropriate, for use in learning activities.Penelitian ini bertujuan untuk mengembangkan bahan ajar IPS model Shared kelas VIII SMP dengan tema Lingkungan dan Kegiatan Ekonomi Masyarakat yang layak, menarik, menumbuhkan kemandirian pada diri siswa dalam pembelajaran berdasarkan hasil uji ahli materi dan ahli media, penilaian guru dan siswa. Metode penelitian yang digunakan adalah metode Research and Development (RD) Borg and Gall. Desain dan prosedur pengembangan modul mengikuti model pengembangan Hilda Taba.Teknik pengumpulan data dilakukan dengan menggunakan teknik wawancara, observasi, dan angket.Teknik analisis data menggunakan analisis data deskriptif kuantitatif yang dinyatakan dalam skor skala lima. Hasil uji kelayakan modul oleh ahli materi memperoleh kategori baik, ahli media memperoleh kategori sangat baik, guru dan siswa memperoleh kategori baik. Berdasarkan uji kelayakan oleh ahli, guru, dan siswa menunjukkan modul IPS model shared kelas VIII sangat sistematis, konsisten, menarik, sesuai, tepat, untuk digunakan dalam kegiatan pembelajaran.Kata Kunci : research and development, modul IPS, dan model shared